Design of Control System for a Desktop Injection Molding Using Raspberry Pi 3 B+ - Rahmat, Rahmat; Putra, Meiki Eru; Amin, Zulkifli (METAL: Jurnal Sistem Mekanik dan Termal, 2023)
Injection molding is one of the techniques used to create plastic items. Plastic goods with good dimensional tolerances are frequently made using the efficient, accurate, and cost-effective injection molding process. The advantages of injection molding include quick product production, accurate process execution, cheap labor costs, automation of the process, and the ability to produce large quantities of items. There are many benefits to using a controller as a measuring device when injection molding. Making injection molding equipment easier to handle and observe is one of them. The process of regulating or controlling one or more quantities (variables) so that they are at a specific objective is known as a control system. In this study, a compact, mobile, automatic plastic injection machine that can create small plastic objects was developed. The design process is developed using the Python programming language, and the control system is a microcontroller of the Raspberry Pi type that has a complete architecture, including wifi and bluetooth modules, as well as a lot of memory. A NEMA 23 stepper motor with a torque of 2.2 Nm and a TB6600 motor driver are used in the drive system to control the voltage and rotation of the motor. A band heater type heating element with a maximum working temperature of 350Â°C at 220 volts is used in the heating system. A desktop program running on a 7-inch TFT display will show the process of controlling and monitoring the device.